Factors Affecting Customer Satisfaction of Mobile Services in Yemen - Mabkhot, Hashed Ahmed Nasser (2010)
The aim of this study is to find out the customer's satisfaction with Yemeni Mobile service providers. This study examined the relationship between perceived quality, perceived value, customer expectation, and corporate image with customer satisfaction. The result of this study is based on data gathered online from 118 academic staff in public universities in Yemen. The study found that the relationship between perceived value, perceived quality and corporate image have a significant positive influence on customer satisfaction, whereas customer expectation is positively related to customer satisfaction but not statistically significance within the selected 5% confidence level.